Kegagalan partai politik baru di Provinsi Jambi 2019 dalam perspektif pelembagaan partai politik - Hatta Abdi Muhammad; Nabil Lintang Pamungkas; Dony Anggara (Publisia: Jurnal Ilmu Administrasi Publik, 2020)
The relationship between institutionalization of party and electoral is an important theme because the strength of institutionalization is demonstrated through party performance in elections. However, the tendency in strengthening party institutionalization can't be separated from the presence of inherent figures. Some literature highlights that institutionalization is a conflicting entity with the emergence of strong figures. This article specifically discusses and explains that the problems of institutionalization and figures can intertwine each other. Because the party's relationship with the electoral arena can't be separated, the need for figures as a reinforcing variable in terms of political contestation, especially new parties in Jambi Province. This article uses descriptive qualitative methods to analyze deeply the phenomena that occur by utilizing secondary and primary data from various informants. Various data is coded, analyzed interactively and confirmed its validity then presented systematically. The results showed that the institutionalization that had been designed by the new parties was not able to produce a significant vote gain. People is more familiar with figures within the party, thus voter preferences see figures more than parties. New parties need to increase their popularity by working with figures that are acceptable to the public. At the end, the author offers how figures can appear in new parties by carrying out a process of political recruitment that emphasizes the involvement of candidates who have the potential to compete in elections.